Linking with farmers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Linking with farmers edited by Carine Alders, Bertus Haverkort and Laurens van Veldhuizen 1993 298pp lSBN 1 853392103 IT Publications 103/105 Southampton Row London WC1B 4HH, UK